2008
DOI: 10.1249/mss.0b013e31817c67a4
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment Correlates of Walking

Abstract: Introduction The past decade has seen a dramatic increase in the empirical investigation into the relations between built environmental and physical activity. To create places that facilitate and encourage walking, practitioners need an understanding of the specific characteristics of the built environment that correlate most strongly with walking. This paper reviews evidence on the built environment correlates with walking. Method Included in this review were 13 reviews published between 2002 and 2006 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

75
1,280
12
50

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 1,594 publications
(1,417 citation statements)
references
References 57 publications
(115 reference statements)
75
1,280
12
50
Order By: Relevance
“…These findings generally align with previous studies that examined environmental correlates of walking. 29 Associations between these five attributes and recreational walking were not moderated by area-level SES, except for residential density being associated with walking specifically in low SES areas. Consistent with other reports indicating that walkability is associated with walking regardless of SES levels, 7-9 this study found that associations between specific environmental attributes and recreational walking are largely similar for low and high SES areas.…”
Section: Discussionmentioning
confidence: 94%
“…These findings generally align with previous studies that examined environmental correlates of walking. 29 Associations between these five attributes and recreational walking were not moderated by area-level SES, except for residential density being associated with walking specifically in low SES areas. Consistent with other reports indicating that walkability is associated with walking regardless of SES levels, 7-9 this study found that associations between specific environmental attributes and recreational walking are largely similar for low and high SES areas.…”
Section: Discussionmentioning
confidence: 94%
“…diversity of destinations, access to shops, access to public transport) (10)(11)(12)20) , accessibility of destinations (e.g. pedestrian infrastructure) (10,12,20) , aspects pertaining to personal safety (e.g. presence of people and safety from crime) (20)(21)(22) and availability of places for sitting (22)(23)(24) would be positively related to walking for transportation.…”
mentioning
confidence: 99%
“…pedestrian infrastructure) (10,12,20) , aspects pertaining to personal safety (e.g. presence of people and safety from crime) (20)(21)(22) and availability of places for sitting (22)(23)(24) would be positively related to walking for transportation. Perceived residential density, crowdedness and traffic load were expected to show a curvilinear, inverted-J relationship with walking for transport.…”
mentioning
confidence: 99%
“…Research in non-diseased populations has shown that increased MVPA was significantly associated with having more pieces of home physical activity (PA) equipment 10,11 and various community characteristics such as reduced crime and access to walking paths. 12,13 Whether similar findings would emerge in a home-based CR population and whether the various perceived environment/MVPA relationships are similar for urban and rural patients remains unknown.…”
Section: Introductionmentioning
confidence: 97%